Gastrointestinal manifestations in a patient with common variable immunodeficiency syndrome. - Mc Namara, Deirdre; Christopher, B.; Ismail, M.S.; Kirca, M. (My University, 2019)
A 57 yo male with a background history of common variable Immunodeficiency syndrome (CVID) on Immunoglobulin Infusion (Kiovig) 40mg three weekly was referred for investigation of diarrhoea and follow up from previous history of colonic polyps. Colonoscopy showed an irregular looking ileocaecal valve (ICV) with an adjacent flat polyp (Paris IIa). Biopsies showed low grade dysplasia. There was also a duodenal polyp noted on gastroscopy and biopsy again showed low grade dysplasia. In light of the findings of upper and lower gastrointestinal tract polyps, a small bowel capsule endoscopy (SBCE) was arranged. This showed an irregular area of mucosa in the proximal small bowel with significant ulceration and inflammation (Figure 1). There were also multiple scattered lymphagiectasias and lymphoid hyperplasia in the distal small bowel (Figure 2). Anterograde double ballon enteroscopy (ADBE) was subsequently performed to the distal jejunum about 8 weeks after the SBCE. The duodenal polyp seen at gastroscopy was visualised during ADBE (Figure 3). In addition, two diminutive (<3mm) jejunal sessile polyps were encountered and excised (Figure 4). There was no evidence of ulcerative enteritis as seen on SBCE. The enteritis features initially visualized on the SBCE was thought to be a transient phenomenon possibly related to his CVID background. However, for completion, the distal point of enteroscopy insertion was marked and a repeat SBCE performed immediately after recovery from the ADBE. This again showed the known duodenal polyp as well as 2 further diminutive small bowel polyps and minimal distal patchy enteritis only, with complete resolution of the previously observed ulcerative jejunitis. The jejunal polyps’ histology was reviewed at a histology multidisciplinary meeting, there were no adenomatous or hamartomatous features and biopsies were thought to have non-specific changes only. The patient was referred for polyp resection and further follow up and surveillance will be arranged based on histology.
PUBLISHED
Keywords: Gastrointestinal manifestations; Common variable immunodeficiency syndrome; CVID; Case report; Immunology, Inflammation & Infection; CVID Syndrome; enteropathy; Health